Studi Kasus Permasalahan Bahasa Pada Aspek Keterlambatan Bicara Anak Usia Dini - Ni Made Sulastri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Language is one of the important aspects in supporting the growth and development of children, one aspect of language development is speech. Speech is an effective communication tool in building social interactions, supporting success in learning and supporting the growth and development of other aspects. In reality, not all children have speech development according to their developmental stages, some experience problems. The purpose of this study is to describe the causes and solutions to speech delays in children aged 5 years. This study is qualitative with a case study approach, data collection techniques in the form of observation, documentation, interviews and field techniques where parents and teachers are the main informants. The results of the activity show that the first factor in speech delay is parenting patterns, where parents tend to fulfill physical needs and do not pay attention to aspects of the child's speech development. Second, the use of bilingualism, in everyday life children at school are more familiar with and accustomed to using Indonesian in communication while at home children with grandmothers and also assisted by caregivers more often listen and communicate in regional languages ​​​​so that confusion occurs in the use of language in children. Third, the lack of interaction in communication, when with parents children are more often active by watching television or playing with mobile phones. The findings are supported by the opinions of experts related to various results obtained in the field, then researchers can provide solutions in the form of providing stimulation with various activities and media that support children's speech, the use of more intensive verbal communication and interaction from parents and the environment. Consultation with experts, teachers and also the provision of speech therapy to support children's language development in the speech aspect